Best Answer

First, you write the equation in its simplest form:

5x + 2 = 3x

Then, you subtract 3x from both sides of the equation, so that the right side has no unknowns left:

2x + 2 = 0

Then, you subtract 2 from both sides of the equation, so that the left side has only a multiple of x left:

2x = -2

Finally, you divide both sides by 2, so that the left side is simply x:

x = -1

Q: How do you solve 5x plus 2 equals 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

23

5x+y=-7 3x+y=15 8=D

172=x

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

Related questions

23

x = -8

3

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

5x+y=-7 3x+y=15 8=D

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

172=x

3x-4=5x+6 gives: 2x=-10 which gives x=-5

5x+8x+3x-2x = 14x

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5